2018
DOI: 10.1093/geroni/igy010
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Major Depression Inventory for Persons With Dual Sensory Loss

Abstract: Background and ObjectivesResearch has shown that dual sensory loss is a risk factor for depression in older adults. However, validated measures of depression for people with dual sensory loss are lacking. The purpose of the present study was to investigate the construct validity and reliability of the Major Depression Inventory for use among elderly persons with acquired dual sensory loss.Research Design and MethodsA cross-sectional questionnaire survey was conducted in a national sample of people ≥50 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
(64 reference statements)
2
13
0
Order By: Relevance
“…While previous studies found high rates of depression and anxiety among adults with sensory impairment and especially among adults with dual sensory impairment, 39‐43 these have been carried out in different countries (UK, Norway, Korea, and Denmark). As different sociocultural backgrounds, environment and healthcare characteristics impact on mental health, it is of importance to study this also in Spanish population.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…While previous studies found high rates of depression and anxiety among adults with sensory impairment and especially among adults with dual sensory impairment, 39‐43 these have been carried out in different countries (UK, Norway, Korea, and Denmark). As different sociocultural backgrounds, environment and healthcare characteristics impact on mental health, it is of importance to study this also in Spanish population.…”
Section: Introductionmentioning
confidence: 98%
“…37 People with dual sensory loss are more likely to be poor and unemployed, and with lower educational outcomes, 38 and consequently may have higher risk of developing mental problems. 39 While previous studies found high rates of depression and anxiety among adults with sensory impairment and especially among adults with dual sensory impairment, [39][40][41][42][43] these have been carried out in different countries (UK, Norway, Korea, and Denmark). As different sociocultural backgrounds, environment and healthcare characteristics impact on mental health, it is of importance to study this also in Spanish population.…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies focused on seven tools for health care assessments and/or interventions to improve health care for older adults with DSI ( Arauz et al, 1997 ; Bruhn & Dammeyer, 2018 ; Dalby et al, 2009 ; Dupuis et al, 2015 ; Hovaldt et al, 2018 ; Roets-Merken et al, 2014 ; Takano et al, 2016 ; Urqueta Alfaro et al, 2019 ; Vreeken et al, 2020 ). Of all the tools reported, five were standardized clinical assessment instruments.…”
Section: Resultsmentioning
confidence: 99%
“…Major Depression Inventory (MDI): The MDI is a self-reporting questionnaire that includes questions about depression symptoms consistent with the DSM-V guidelines for major depressive disorder. The MDI is commonly used in research to determine the degree to which an individual is currently experiencing a depressed mood and has shown to have high sensitivity, specificity, validity, and test-retest reliability for patients with low back pain [ 66 , 67 ]. Participants who score above a 30, indicating severe depression symptoms, will be sent a referral for medical management.…”
Section: Methodsmentioning
confidence: 99%